DEVOLOPİNG İNCLUSİON İN EDUCATION. - Qocayeva Nurana Mammad (Theoretical Hypotheses and Empirical Results, 2025)
Education, which is accepted as a fundamental human right according to the Universal Declaration of Human Rights, started to include the concepts of social justice and equality with the Salamanca Declaration (UNESCO, 1994). According to this statement, education should have a structure that focuses on the individual differences of students and the needs brought about by these differences. Today, the structure of schools becomes more diverse and more students with different needs take part in the education process. In this case, it is a universally accepted fact that education is offered equally for all. However, the issue of how to provide this education is still debated. The ecological model, on the other hand, examines individuals by including their political and socio - economic systems and responds to their needs. The ecology of inclusive education examines the effects of systems on the education process while evaluating students as valuable and participatory individuals. In this study, inclusive education is presented from an ecological model perspective. In this context, by explaining the features of inclusive education and ecological models, the systems of the ecological model are explained with an inclusive education perspective.